PRESENSI SISWA MENGGUNAKAN QR CODE DAN SMS BROADCAST BERBASIS WEB - Sherly Christina; Agus Sehatman Saragih; Fahrizal Maulana (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2019)
Student attendance is one of the factors that need to be controlled by the School to maintain Indonesian resources. Therefore a school needs a system that can be used, for handles the students attendance data and distributes it to the parents. This necessity can be facilitated by building an online attendance system for the students. The online attendance system uses QR Code and Broadcast Short Message Service (SMS). The online attendance system used Waterfall methodology phases as the system development phases. Afterward the system performance is evaluated using the black-box testing. The results test using black-box testing show that the system can accomplish the purpose of this research to meet the need of the School in collecting the student attendance data and distributing the information of the students attendance data to the parents. This system uses QR Code and the results of collecting the student attendance data are sent by the system through Broadcast SMS to parents.